Development of the Protection Against Osteoporotic Fractures Scale - Sultan Aydın; Mehmet Ali Kurçer; Zeynep Erdoğan (Galenos Yayinevi, 2021)
Objective:Osteoporosis is a bone disease that increases the risk of fractures. One out of every two women and one out of every five men are at risk for osteoporosis-related fractures during their lifetime. Bone loss can be prevented by taking precautions in every phase of life. To avoid the serious consequences of osteoporosis, healthy behaviours should be supported using theories of health behaviour as a framework. This study aimed to develop protection against osteoporotic fractures (PROF) scale and to test its validity and reliability.Materials and Methods:This study was conducted among >55-year-old female outpatients who were admitted to the orthopaedic clinics of Zonguldak Atatürk Public Hospital. Test-retest was applied via face-to-face interviews. The sample size was calculated to be 10 times the number of scale items, resulting in a sample of 400 participants. The theory of planned behaviour provided the theoretical framework for the PROF scale development. Four strategies have been selected for PROF: (1) Bone mineral density measurement, (2) adherence to treatment, (3) physical exercise and (4) regulations to prevent falls at home.Results:Factor and matrix correlations of the scale ranged from 0.68 to 0.130. Test-retest reliability of the whole scale was 0.95. Cronbach's α value was found to be 0.95. A strong and statistically significant positive correlation was noted between attitudes and subjective norms pertaining to PROF (r=0.520; 0.525; p=0.01, respectively). A moderate and statistically significant positive correlation was noted between intention and behaviour control (r=0.462; p=0.01).Conclusion:The PROF scale was found to be highly valid and reliable. It can be a part of the public health model aimed at preventing osteoporotic fractures.